Advances in biosensors for wastewater quality assessment - Sharifi, Maryam; Pourasl, Mehri H.; Tajalli, Habib; Khalilzadeh, Balal; Isildak, Ibrahim (ELSEVIER SCI LTD, 2026)
Contamination of wastewater presents a major risk to global water resources, ecosystems, and human health, driven by industrial discharges, agricultural runoff, and inadequate sanitation infrastructure. Key pollutants, such as heavy metals, organic compounds, pathogens, and emerging pollutants like pharmaceuticals, are analyzed for their effects on aquatic ecosystems and public health. Conventional methods including titration, spectrophotometry, gas chromatography, high-performance liquid chromatography, ion chromatography do not have enough sensitivity for timely diagnosis. So sensitive, fast and available diagnostic devices are highly needed for pollution detection. Biosensors compared with the conventional methods, they have many advantages such as sensitive, specific, low cost and rapid. This review evaluates the role of biosensor technologies in detecting and monitoring of wastewater pollutants, highlighting their potential for real-time, sensitive, and cost-effective analysis. Also, the types of biosensors used to monitor of water pollution were reviewed and compared with conventional methods and their pros and cons were discussed.
Keywords: Biosensor; Wastewater pollution; Nanoparticles; Aquatic ecosystems; ELECTROCHEMICAL BIOSENSOR; SELECTIVE DETECTION; ESCHERICHIA-COLI; OXYGEN-DEMAND; REMOVAL; SENSOR; DICLOFENAC; OXIDATION; ELECTRODE; EXPOSURE; Chemistry